2015
DOI: 10.1108/par-12-2013-0104
|View full text |Cite
|
Sign up to set email alerts
|

Company characteristics and compliance with ASX corporate governance principles

Abstract: Purpose – This study aims to examine whether company characteristics determine the structure and composition of a company’s board. In particular, it investigates the three board-design choices that Australian-listed companies make in the context of Australian Stock Exchange (ASX) corporate governance principles (published in 2003) where they are allowed to depart from the recommended best-practice board structure if the departure better serves their unique board and governance requirements. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Other predictors; include workforce, years of establishment and assets of SMEs. The findings of this study align with Lama and Anderson (2015), Okafor (2007), Shittu et al (2016) and consistent with institutional theory (DiMaggio and Powell, 1983;Meyer and Rowan, 1977;Oliver, 1991;Zucker, 1987).…”
Section: Effects Of Organizational Characteristics On Smes Covid-19 Workers Commitmentssupporting
confidence: 88%
See 2 more Smart Citations
“…Other predictors; include workforce, years of establishment and assets of SMEs. The findings of this study align with Lama and Anderson (2015), Okafor (2007), Shittu et al (2016) and consistent with institutional theory (DiMaggio and Powell, 1983;Meyer and Rowan, 1977;Oliver, 1991;Zucker, 1987).…”
Section: Effects Of Organizational Characteristics On Smes Covid-19 Workers Commitmentssupporting
confidence: 88%
“…Studies revealed that although the central idea of institutional theory is isomorphic behavior, organizations differ in their strategic responses to institutional forces, organizations may decide to avoid, compromise, defy and manipulate the institutional environment based on organizational characteristics. (Lama and Anderson, 2015;Moser et al, 2020;Oliver, 1991;Shittu et al, 2016). Institutional theory has been projected to be a suitable lens to examine the dynamics of organizational strategic responses to regulations (Moser et al, 2020;Raynard et al, 2015).…”
Section: Conceptual Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, examining smaller companies in an Australian voluntary compliance setting contrasts with prior research conducted in the United States (Anderson and Bizjak, ; Vafeas, ; Sun and Cahan, ; Sun et al ., ; Conyon, ) where requirements for remuneration committee formation and independence are mandatory and the general regulatory environment differs substantially (Monem and Ng, ) . Empirical evidence indicates that a one size fits all regulatory approach is inefficient because optimal governance arrangements vary significantly across companies (Christensen et al ., ; Lama and Anderson, ) and the costs of compliance can significantly outweigh benefits (Linck et al ., ; Dhole et al ., ). Therefore, examining the effects of voluntary adoption of the ASX remuneration committee recommendations provides useful information regarding the choice between a voluntary and mandatory regulatory policy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ASX has provided no information about factors that may have caused these rates to occur, thereby shedding little light on treatment by firms of the explanation requirement. Lama and Anderson (2015) found on a sample of ASX firms, with respect to board-member independence and CEOboard chair separation, that smaller firms and firms with shareholdings concentrated in ARJ 32,2 relatively fewer hands had a lower rate of compliance but the authors did not investigate the nature of responses made when an explanation was called for.…”
Section: Literaturementioning
confidence: 99%